2012
DOI: 10.1177/2151458512450708
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Complications and Length of Hospital Stay Between Orthopedic and Orthogeriatric Treatment in Elderly Patients With a Hip Fracture

Abstract: Hip fractures in the elderly individuals are a complex problem. Our objective was to determine whether orthogeriatric treatment is effective in terms of reducing length of hospital stay, morbidity, and mortality of elderly patients with a hip fracture compared with orthopedic (traditional) treatment. From July 2009 to May 2011, patients older than 65 years with a hip fracture were followed prospectively. They were co-treated by geriatric and orthopedic teams. This cohort was compared with a retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 11 publications
2
23
0
2
Order By: Relevance
“…In many studies, mortality after hip fractures has been reported as 20–30%. [3,6,7,12] .This high mortality rate is due not only to trauma or major surgery but also to co-existingcardiac, pulmonary or renal diseases, old age and preoperative cognitive dysfunction [3–5, 1215]. Elderly patients are particularly prone to mortality in the first year after a hip fracture with mortality rate ranging from 14% to 36% [1,6,7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, mortality after hip fractures has been reported as 20–30%. [3,6,7,12] .This high mortality rate is due not only to trauma or major surgery but also to co-existingcardiac, pulmonary or renal diseases, old age and preoperative cognitive dysfunction [3–5, 1215]. Elderly patients are particularly prone to mortality in the first year after a hip fracture with mortality rate ranging from 14% to 36% [1,6,7] .…”
Section: Discussionmentioning
confidence: 99%
“…Wagner reported that 25% of patients with a hip fracture become dependent on nursing, 50% recover to preoperative status and the remaining 25% die, usually within the first year postoperatively [6]. Male gender, increasing age, cognitive function impairment and high ASA scores have been found to be significantly associated with mortality in these patients [7] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, approximately 150,000 adults were hospitalized for hip fracture in Japan, and this number is expected to increase with the aging of the population [2]. Elderly patients often have multiple comorbidities before hip fracture, and are considered to be at a high risk of postoperative complications [3].…”
Section: Introductionmentioning
confidence: 99%
“…La estancia media de 10,2 días está cercana a las medias más bajas encontradas en la literatura revisada (21)(22)(23)25,26) , aunque no es fácil la comparación con otros teniendo en cuenta que en algunos casos se incluye en la estancia media los primeros días de rehabilitación.…”
Section: Discussionunclassified
“…El diagnóstico más frecuente, fractura de sección trocanterea neom de cuello de fémur cerrada, es una fractura extracapsular, lo que está en consonancia con lo revisado (2,19,(21)(22)(23)(24) . La estancia media preoperatoria, de 3,5 días, es acorde con la mediana en España que se sitúa alrededor de los 3 días.…”
Section: Discussionunclassified